Friedrich Carl Von Savigny’s Thoughts on The Existence of Annual Sale and Purchase Customary Love Establishment - Nadir Nadir (International Journal of Law and Society, 2025)
This research aims to reveal stability Friedrich Carl Von Savigny’s thoughts on the existence of annual sale and purchase customary love establishment. This research uses legal research methods, namely research carried out on legal norms that develop in society. The approach used is a conceptual and historical approach. The types and sources of data used in this research are primary and secondary data. The results of this research show that the teachings of the historical school initiated by Von Savigny emphasize that law is a reflection of the soul of the people that grows together with the people’s growth of the people and becomes strong together with the people’s strength. Furthermore, in the end, it dies if the nation loses its nationality. Thus, adherents of the historical school reject the view that law is made by an authorized institution, such as by making laws. Meanwhile, customary law that exists in Madurese society as the customary law of the Madurese people in some villages, such as “annual purchase and sale,” as the customary law of the community is maintained in the practice of annual purchase and sale of a plot of land that is perhaps not found in other areas in Indonesia. It is similar to the historical school, namely that law grows together with the growth of society and becomes strong together with the strength of society. Furthermore, in the end, it dies if the nation loses its nationality. This condition is recognized as existing by the constitution of the Indonesian legal state as regulated in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia.